A comparison of clinical characteristics of older adults treated with antidepressants in general and psychiatric hospitals in Asia. Issue 6 (21st April 2017) - Wang, Yuan‐Yuan; Xiang, Yu‐Tao; Ungvari, Gabor S.; Ng, Chee H.; Chiu, Helen F.K.; Yim, Larina C.L.; Si, Tian‐Mei; Chee, Kok‐Yoon; Avasthi, Ajit; Grover, Sandeep; Chong, Mian‐Yoon; Sim, Kang; et al.
Abstract : Aim: This study compared the demographics, clinical characteristics, and antidepressant prescription patterns between Asian patients aged 50 years and older attending psychiatric hospitals and those attending general hospitals. Methods: In total, 955 patients (604 in general hospitals, 351 in psychiatric hospitals) aged 50 years or older treated with antidepressants in 10 Asian countries and territories were examined. Patients' demographics, clinical features, and prescriptions of psychotropic drugs were recorded using a standardized protocol and data collection procedure. Results: Binary logistic regression revealed that high income and diagnosis of schizophrenia were independently associated with psychiatric hospital treatment, whereas outpatient care, diagnosis of anxiety disorders, and multiple major medical conditions were independently associated with general hospital treatment. In addition, tetracyclic and noradrenergic and specific serotonergic antidepressants were more likely to be prescribed in general hospitals. Conclusion: Older adults treated with antidepressants showed different demographic and clinical features between general hospitals and psychiatric hospitals in Asia.